Analisis Certainty Factor Dalam Mendiagnosa Tipe Diabetes Berbasis Web - Kartika Sari; Rosma Siregar; Astri Syahputri (Journal of Information System Research (JOSH), 2022)
This study discusses certainty factor analysis to diagnose diabetes mellitus (DM) which is implemented in a smart system that aims to make it easier for people to know the type of diabetes. A person's lifestyle is the main thing in maintaining health, but if you have an unhealthy lifestyle, it will cause disease. One of the many diseases caused by an unhealthy lifestyle is diabetes mellitus. The system built in this research will be implemented using the certainty factor (CF) method. Users can choose what symptoms are experienced on the system, where the symptoms are obtained from an expert. The output of this expert system is to diagnose the user as having type 2 diabetes mellitus. This research yielded 84% results. The purpose of this study is to help the community in diagnosing the type of diabetes experienced so that they can get the right treatment.